‎“Parents Who Cause Harm”: A Study of the Attachment Theory in Christopher Durang’s ‎‎‘The Marriage of Bette and Boo’‎ - Abbas, Zainab Khudhair; Mohammed, Marwa Ghazi (Dirasat: Human and Social Sciences, 2025)
Objectives: This study aims to examine toxic parental behavior and its impact on children based on the attachment theory. It also explores how early parental relationships influence future relationships with partners and children. The research assesses types of toxic parenting (dysfunctional, harmful, and psychologically damaging parenting behaviors) and their resulting insecure attachment patterns—avoidant, ambivalent, and disorganized—through the characters in The Marriage of Bette and Boo. Methods: Toxic parents play a decisive role in children’s lives, affecting how they view themselves and impacting their behavior. The study uses a psychological evaluation method that relies on the attachment theory (1978), first presented by John Bowlby and later developed by other theorists. It examines the type of attachment that a child forms with his parents in his early years and how that pattern will affect his future relationships. Results: The play's analysis of toxic parenting, framed by the attachment theory, affirms that insecure parenting environments can lead sons to develop an avoidant attachment to their parents and their beliefs. Matt's avoidant attachment, which stems from his relationship with toxic parents, has shaped his idiosyncratic worldview and religious beliefs through emotional detachment from others. Conclusions: The study demonstrates how toxic parenting causes insecure attachment patterns in children. It concludes that toxic parenting affects every aspect of a person's life, including their relationships with their partners and children. It also demonstrates that insecure parents raise insecure children.